Pengaruh Modifikasi Permainan 4-1 Kucing Bola Terhadap Ketepatan Passing Bagian dalam Pada Kegiatan Ekstrakulikuler Futsal Madrasah Aliyah (MA) di Masa Pandemi Covid-19 - Imam Maulana Hafazhah; Ega Trisna Rahayu; Rizki Aminudin (Peneliti.net, 2021)
The purpose of this study was to determine whether the modification of the 4-1 cat ball game has an influence on the accuracy of inner passing during the COVID-19 pandemic. This research is included in quantitative research using the experimental method of one group pre-test-posttest design with 10 treatments. The population and sample used were purposive sampling with a total of 14 futsal extracurricular students. The instrument used is the passing accuracy test in Sebagyo Irianto (1995: 9 The t-count value is 11,541, the t-table is 2.16, and the significance value is 0.000 <0.05. It shows that